Hubungan Antara Pengelolaan Sampah Rumah Tangga dan Kualitas Kesehatan Lingkungan Permukiman - Ahda Ahda; Ernyasih Ernyasih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Household waste management is an important part of maintaining environmental quality. This article is a literature review that aims to identify and analyze the relationship between household waste management and its impact on environmental quality. The purpose of this study is to gain a better understanding of the extent to which household waste management behaviors and systems can affect environmental conditions and public health. The method used is a systematic literature review of various scientific journals, research reports, and policy documents published in the last ten years. Data sources were taken from academic databases such as Google Scholar, ScienceDirect, and PubMed, with a focus on studies discussing aspects of waste management, sanitation, and health impacts in residential environments. The results of the study show that poor urban waste management, such as littering and open burning, is associated with an increase in environmental diseases. Conversely, good management systems, such as regular sorting and transportation, have a positive impact on the cleanliness and health of the residential environment. Conclusion Good household waste management plays an important role in maintaining a healthy living environment. Organized and participatory practices can reduce the risk of disease and create a clean, healthy, and sustainable environment for communities.